Towards a Better Distance Learning: Experience of Radiologic Technology Students in a Higher Education Institution - Said, Mariam Hadji; Dalug, Normylene; Galawan, Nihayah; Hibaya, Harold Jay; Jenan , Jenan (Future Science / FSH-PH Publications, 2022)
Radiologic Technology students are among those who felt the intensity of drastic changes brought by the pandemic in education, particularly when distance learning was utilized. The main objective of this study is to find out the varied experiences of the selected students and find out the necessary measures that need to be taken to address the emerging issues that surround distance learning. This phenomenological qualitative research was done by interviewing the selected respondents from Iligan Medical Center College, transcribing their answers, and utilizing thematic analysis to find out the recurring themes. The respondents of this research were the eight selected students, who were enrolled in Radiologic Technology program. There were two respondents taken from each year level and interviewed online. The responses taken from the interview transcripts were grouped and labelled according to their semantic similarities. The researchers found out that the current distance learning practices of Iligan Medical Center College include online-synchronous and online-asynchronous learning. The students’ main problems regarding this type of education include their teachers’ lack of knowledge on technology utilization, financial constraints, internet connection problems, lack of focus on their lessons, their vulnerability to cheating, and the health issues and problems. Moreover, the coping strategies of the students to the problems they encounter in distance learning include time-management and getting support from the significant persons around them. In addition, the students assert that the school administration should monitor the teachers even more and improve their digital skills in order for them to relay the lessons more efficiently and effectively. Furthermore, they also emphasized that the teachers’ discussion should be livelier in order to encourage active learning and that they should be more considerate and patient, especially when the students try to approach them for something that they did not understand. In addition, the students also believed that the teachers should practice more in using their technological resources. Generally, data from this research imply that the distance learning will be even more successful if there is a proper preparation and training for both the teachers and students. Also, there should be an intervention program that will help the students in dealing with their mental and health issues.